2021
DOI: 10.1177/17562864211007708
|View full text |Cite
|
Sign up to set email alerts
|

Hypoechogenicity of the midbrain raphe detected by transcranial sonography: an imaging biomarker for depression in migraine patients

Abstract: Background: The high comorbidity of migraine and depression is suggestive of shared risk factors or common mechanisms between the two diseases. In individuals with a depressive disorder, there is a high prevalence of altered midbrain raphe (MBR) echogenicity, detectable via transcranial sonography (TCS), that is suggested to be linked with a dysfunction of the serotoninergic system. In patients with migraine, this alteration has seldom been explored in earlier studies, and conclusions are often lacking. Our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
2
9
2
Order By: Relevance
“…15 To date, two of four studies exploring the association of hR with migraine have shown a higher prevalence of hR compared to controls. [16][17][18][19] Importantly, in one of the two studies not showing higher prevalence of hR, migraine patients with history of depression were excluded from the study, which might explain the lower prevalence of hR in this study. 16 In migraine patients, the presence of hR has been associated with higher scores on depression scales, 20,21 higher frequency of attacks, 16 and greater use of analgesics.…”
Section: Introductionmentioning
confidence: 90%
“…15 To date, two of four studies exploring the association of hR with migraine have shown a higher prevalence of hR compared to controls. [16][17][18][19] Importantly, in one of the two studies not showing higher prevalence of hR, migraine patients with history of depression were excluded from the study, which might explain the lower prevalence of hR in this study. 16 In migraine patients, the presence of hR has been associated with higher scores on depression scales, 20,21 higher frequency of attacks, 16 and greater use of analgesics.…”
Section: Introductionmentioning
confidence: 90%
“…While the SSS was not assessed in patients with depression, this finding is of note and may potentially point towards diversity in the pathomechanism of FMS and depression. As for the seemingly contradictory data in our study to published literature regarding reduced midbrain echogenicity in patients with depressive symptoms it is of note that we investigated patients with a psychiatrically confirmed diagnosis of depression, while in other studies, mainly patients with another primary disease such as migraine [ 30 ] or Parkinson`s disease [ 34 ] were studied who additionally had depressive symptoms. Hence, data may differ between patients with depression and those with mere depressive symptoms.…”
Section: Discussionmentioning
confidence: 82%
“…The finding of reduced echogenicity in the midbrain raphe region is well reproduced in patients with depression [ 15 , 24 26 ], migraine [ 16 ], panic disorders [ 13 ], and obsessive-compulsive disorder [ 27 ]. Several studies also reported a correlation of raphe echogenicity with additional depressive symptoms in the respective primary disease such as in epilepsy [ 28 ], Parkinson`s disease [ 29 ] or migraine [ 30 , 31 ]. However, data are controversial [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, migraine studies may need to consider depression when interpreting functional magnetic resonance imaging data (Ma M, Zhang J, Chen N, et al, 2018). In a randomised controlled trial (Zhang Y, Liu Y, Han R, et al, 2021), depressive symptoms were assessed by transcranial sonography and the Hamilton Depression Rating Scale (HAM-D) in a migraine group, a tension headache group and a healthy control group, and the results showed that midbrain raphe (MBR) hypoechogenicity was 28% higher in the migraine group than in the healthy and tension headache groups. This suggests that midbrain raphe hypoechoic abnormalities detected by transcranial sonography may be an imaging biomarker for patients with migraine and depression.…”
Section: Connections Of Brain Structurementioning
confidence: 99%